Association of habitual physical activity with depression and anxiety: a multicentre cross-sectional study - Li Huang; Xudong Liu; Sitong Liu; Yunting Mei; Yuandi Xi (BMJ Open)
Objective Despite the known benefits of physical activity, the effect of habitual physical activity (HPA) on depression and anxiety remains unclear. This study aimed to investigate the association of HPA with the risk of depression and anxiety among Chinese adults, with the consideration of disease severity.Methods The participants in this multicentre cross-sectional study were from the nationwide survey of the psychology and behaviour of Chinese residents. Depression and anxiety were measured using the nine-item Patient Health Questionnaire and seven-item Generalised Anxiety Disorder scale. HPA was assessed by the short form of the International Physical Activity Questionnaire. Crude and adjusted ORs with their 95% CIs were estimated by using ordinal logistic regression.Results Of the 19 798 participants, 3901 (19.7%) had anxiety and 8914 (45.02%) had depression. Compared with inactive participants, depression risk in individuals reporting low, median and high volume HPA was reduced by 23% (OR 0.77, 95% CI 0.66 to 0.89), 21% (OR 0.79, 95% CI 0.68 to 0.90) and 13% (OR 0.87, 95% CI 0.78 to 0.98), respectively, after adjustment for confounder. No significant association of HPA with anxiety risk was observed.Conclusion Participation in HPA, whether low, median or high volume, was associated with a lower risk of depression compared with inactive participation, while no significant association was observed between HPA and anxiety.